The Role of Entrepreneurial Marketing in Achieving Strategic Agility An Analytical Study of Managers' Opinions in a Sample of Private Sector Banks in Sulaymaniyah, Iraq - Daroon Faridun Abdullah; Dunya Ahmed Abdullah; Roza Ahmed Hama Amin (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
The current research aims to identify the role of entrepreneurial marketing with its dimensions (maximizing resources, opportunities-driven, risk management, Innovation, creating value for the customer) in achieving strategic agility via its dimensions (strategic sensitivity, leadership unity, flow of resources) in private banks sector in the Sulaymaniyah city- Iraq. After reviewing a set of studies and literature, the conceptual framework, study models and hypothesis were written based on entrepreneurial marketing and strategic agility. The questionnaire was used as a tool to collect the data, and was distributed to managers and heads of unities in a sample of banks in the private sector in the Sulaymaniyah city, with number (50) person. Several tests were conducted before and after the distribution of the questionnaire in order to verify its validity, reliability, and to ensure its validity in measuring the study variables such as the validity, reliability (Cronbach’s alpha), using the SPSS v21 program. In order to measure the strength of correlation and regression between the study variables, several statistics methods were used including simple correlation analysis and simple linear regression. The results showed that there is a relationship and positive effect between the variables and their dimensions. Based on the results, a number of recommendations were given regarding the need for the private banks to focus on adopting entrepreneurial marketing in order to achieve strategic agility and adaptation to the turbulent banking environment.